Subcutaneous abscess due to empyema necessitans caused by Porphyromonas gingivalis in a patient with periodontitis - Akane Tanaka; Mariko Kogami; Yoko Nagatomo; Yukihisa Takeda; Hiroya Kanzawa; Yohei Kawaguchi; Shotaro Ono; Kinya Furukawa; Hiroyuki Nakamura; Kazutetsu Aoshiba (IDCases, 2022)
Empyema necessitans is a rare empyema complication characterized by an extension of empyema out of the pleural space into the subcutaneous tissues of the chest wall. We herein report a case of empyema necessitans that presented as a subcutaneous chest wall abscess caused by Porphyromonas gingivalis (P. gingivalis), an important anaerobic periodontal pathogen, in a 74-year-old woman with periodontitis. The patient was admitted to our hospital with a painful soft tissue mass in the chest wall extending from a subpleural lung abscess associated with empyema. Exploratory percutaneous puncture and aspiration of the chest wall mass yielded foul-smelling chocolate-colored pus, which was found to be caused due to infection with P. gingivalis. Treatment with antibacterials resulted in a relapse of empyema necessitans requiring a second admission 1 month later. An additive treatment with surgical open drainage and decortication of the subcutaneous abscess successfully cured the abscess. Physicians must be aware of emphysema necessitans as an etiology of a chest wall mass and should consider periodontitis as a source of infection.